Male and female reproductive success in natural and anthropogenic populations of Malaxis monophyllos (L.) Sw. (Orchidaceae) - Jermakowicz, Edyta; Ostrowiecka, Beata; Tałałaj, Izabela; Pliszko, Artur; Kostro-Ambroziak, Agata (Biodiversity: Research and Conservation, 2015)
In the presented study, male and female reproductive success was analyzed in relation to the population size, floral display and pollinators’ availability in natural and anthropogenic populations of the orchid Malaxis monophyllos (L.) Sw. Our results indicated significant differences between all investigated populations in parameters of floral display, including heights and number of flowers per inflorescence, as well the number of flowering individuals and their spatial structure. Additionally, populations differed both in male (pollinia removal) and female (fruit set) reproductive success, but only the fruit set clearly differentiated anthropogenic and natural populations. Despite the average flower number per plant being significantly higher in two of the anthropogenic populations, it was not related to the fruits set, which was significantly lower there. Moreover, our preliminary study concerning the potential pollinators of M. monophyllos showed a higher contribution of flies in natural habitats than in anthropogenic ones. Thus, we can suspect that the main factors influencing the level of female reproductive success in M. monophyllos populations are abundance of effective pollinators, as well as flower visitors, which may have resulted in a different level of pollen discounting in populations. Therefore, further studies concerning breeding system and pollination as important forces that shape demographic processes in M. monophyllos populations are necessary. Our results also indicate that suitable conservation methods in M. monophyllos should always include the preservation of potential pollinators, especially in these new, secondary habitats.